Investigation of the effect of butanol and ethanol alcohols on the combustion, performance and emission of diesel-biodiesel blends - Hassan, Md Mahmudul (2018)
Recently the use of renewable fuels in the compression-ignition engine is getting more and more attention to reduce the dependency on fossil oil-based energy resources all over the world. Energy security and global warming alarm which are the two main driving forces for the global energy development nowadays. Alcohol blend fuels are now trying to fill in these demands. In this research work, the experimental investigation on the effect two alcohol additions in the diesel-biodiesel blends on combustion, performance, and emission of a direct injection diesel engine is stated. Moreover, the diesel-biodiesel blends are also investigated. These alternative fuels are employed: B5 (diesel -95%, biodiesel-5%), B20 (diesel -80%, biodiesel-20 %), D80PB5BU15 (diesel -80%, biodiesel-5 %, Butanol-15%) and D80PB5E15 (diesel -80%, biodiesel-5 %, Ethanol-15%), to compare their performance against (D100) pure diesel. The alternative fuels were identified, and their properties were tested to analyse the fuel quality. All the experimental tests were conducted by a single cylinder Yanmar TF-120M diesel engine was used by varying the engine loads (low load, half load and full load) at constant speed of 2400 rpm and variable engine speeds (1200 rpm, 1800 rpm, 2100 rpm) at constant half load conditions. The discussion will focus on combustion characteristics, performance and emissions. The results show the alcohol blends of butanol and ethanol has promising impact especially in the emissions. From performance analysis the thermal efficiency had increased by 1.13%, while fuel consumption 1.86% for D80PB5BU15.The EGT also shown some impacts while using the alcohol blends. Furthermore, results have reported that the diesel engine has reduced the emission NOx reduced (8.02-36) %, CO reduced (16.6-40) % and CO2 reduced (8.02-36) % emissions under different ranging engine load and speed influence while using the butanol and ethanol alcohol blends at diesel bio diesel blending. So, it was found that the alcohol blends shown the promising result which can be positive impact both as an alternative fuel and the environmental aspect.